The Importance of Stroma and Stromal SMA Expression in Pancreatic Ductal Adenocarcinoma - Gamze AKBAS; Pelin BAGCI (Federation of Turkish Pathology Societies, 2024)
Objective: Pancreatic stellate cells (PSC) have been defined to be the key players in pancreatic fibrogenesis and carcinogenesis. They undergo myofibroblast-like differentiation, express α-smooth muscle actin (α-SMA), and play a crucial role in injury and inflammation sites. This study aims to evaluate the relationship between α-SMA expression and histopathological parameters of pancreatic ductal adenocarcinoma (PDAC), and investigate their association with prognosis. Material and Methods: Eighty-one consecutive pancreatectomies diagnosed as usual pancreatic ductal adenocarcinoma were included. The stromal density was scored as loose, moderate, or dense, and α-SMA expression was evaluated immunohistochemically. Results and Conclusion: Mean survival was 19.6 months. Male gender, larger tumor diameter (>3.7 cm), and older age (>64 years) were identified as independent poor prognostic factors. Perineural invasion significantly effected survival. A statistically significant correlation was found between high α-SMA expression and the presence of angioinvasion (p=0.01). Stromal α-SMA expression in PDAC may help determine the risk of angioinvasion.